Peran Merek Dagang dalam Strategi Manajemen Pemasaran Perspektif Hukum Ekonomi Syariah - Rasyid, St. Cheriah; Pikahulan, Rustam Magun; Hasniati; Rasdiyanah (Fakultas Syariah IAIN Kendari, 2025)
Registered trademarks provide exclusive rights to their owners to protect their products or services from imitation and unfair competition. However, many MSME (Micro, Small, and Medium Enterprises) owners still do not understand the importance of trademark registration, perceiving that trademarks are only relevant for large companies and feeling that the registration process is complicated and costly. This research employs a qualitative method with a case study approach, conducting in-depth interviews with MSME owners in Parepare City and analyzing documents related to trademark registration. The research findings show the crucial role of trademarks in supporting product differentiation, enhancing competitiveness, and building consumer trust in MSME products. In addition, this article also examines the application of the principles of Islamic economic law in trademark protection, emphasizing the values of justice, transparency, and honesty in business. This study suggests that the government and related institutions should improve education and simplify the trademark registration process to support the development of MSMEs in Parepare City. By doing so, MSMEs are expected to more easily protect their trademarks, strengthen their product image, and increase their competitiveness in an increasingly competitive market. Keywords: Trademark Protection, MSMEs, Parepare City, Islamic Economic Law, Product Differentiation